2021
DOI: 10.1371/journal.pone.0260230
|View full text |Cite
|
Sign up to set email alerts
|

To vaccinate or not to vaccinate!? Predictors of willingness to receive Covid-19 vaccination in Europe, the U.S., and China

Abstract: Researcher teams around the globe including the “Project Lightspeed” are intensively working on vaccines to fight the Covid-19 pandemic. However, the availability of effective vaccines does not guarantee the vaccination willingness among the population. In spring 2021, we investigated the vaccination willingness and its potential predictors in representative online samples in nine countries (China, France, Germany, Poland, Russia, Spain, Sweden, U.K., U.S.). Of the 9,264 participants, 79.9% revealed Covid-19 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 87 publications
0
31
1
Order By: Relevance
“…Elliott and colleagues found a lower intent to vaccination in women than in men [ 18 ]. An international survey on willingness to receive the COVID-19 vaccination showed a higher propensity in men than women in Germany, France, Russia, and the US, but not in China, where men were more hesitant than women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elliott and colleagues found a lower intent to vaccination in women than in men [ 18 ]. An international survey on willingness to receive the COVID-19 vaccination showed a higher propensity in men than women in Germany, France, Russia, and the US, but not in China, where men were more hesitant than women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the vaccines against COVID-19 were not available yet, and the vaccination campaign started at the end of December 2020. Although a comprehensive vaccination against COVID-19 could help reduce socioeconomic inequalities, several studies investigated the characteristics associated with the willingness to receive the vaccination against COVID-19 [ 15 , 16 , 17 , 18 , 19 ], showing greater hesitancy in the disadvantaged groups of the population.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very critical concern because urban dwellers are largely educated with a significant presence on several social media platforms [ 41 ]. In some previous studies, several authors have reported negative association between social media exposure and the acceptance of COVID-19 vaccines [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ], while others reported positive association [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues [ 24 ] highlight that demographic characteristics are key factors driving people’s behaviors to receive the COVID-19 vaccine. Sociodemographic characteristics such as age, sex, education level, mental health, and ethnicity significantly affect the willingness to receive the vaccine [ 25 , 26 , 27 ]. Moreover, healthcare workers and individuals considering themselves at risk of disease were more likely to self-report acceptability to receive a COVID-19 vaccination [ 28 ].…”
Section: Introductionmentioning
confidence: 99%